Implementation of the Independent Curriculum in Increasing Learning Effectiveness at MI Al Muta'alimin Sukagumiwang - Lili Indriyani; Rizal Rahmawan Muis; Ria Yulia Gloria; Iis Arifudin; Sopidi Sopidi (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to examine the implementation of the Independent Curriculum at MI Al-Muta'alimin Sukagumiwang and its influence on learning effectiveness. The Independent Curriculum emphasizes student-centered learning, differentiated learning, and projects to strengthen the Pancasila Student Profile (P5), thereby encouraging character development, creativity, and critical thinking skills. This study uses a qualitative approach with a case study design, with informants consisting of madrasah heads, teachers, students, and education personnel selected through purposive sampling. Data is collected through interviews, observations, and documentation, then analyzed through data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of the Independent Curriculum is carried out in stages through the preparation of teaching modules and Learning Objectives Flow (ATP), project-based learning, as well as formative assessments and descriptive reporting. This approach improves student engagement, learning motivation, quality of teacher-student interaction, understanding of essential materials, and strengthening character and social skills. Factors that affect the effectiveness of the curriculum include teacher readiness, facilities, school leadership, school culture, parental and community support, government policies, quality of teaching materials, learning approaches, and student readiness. To optimize the implementation of the Independent Curriculum, it is necessary to increase the capacity of teachers and school management, effective socialization, development of learning resources, and continuous monitoring and evaluation.